2013
DOI: 10.1371/journal.pone.0072775
|View full text |Cite
|
Sign up to set email alerts
|

The Microbial Spectrum of Neonatal Sepsis in Uganda: Recovery of Culturable Bacteria in Mother-Infant Pairs

Abstract: Neonatal sepsis in the developing world is incompletely characterized. We seek to characterize the microbial spectrum involved in sepsis and determine the role of maternal transmission by comparing organisms that can be cultured from septic newborn infants and their mothers. From 80 consecutive mother-infant pairs meeting clinical criteria for neonatal sepsis, we collected infant blood and spinal fluid, and maternal blood and vaginal specimens. Identifiable bacteria were recovered from the blood in 32.5% of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 25 publications
3
59
1
Order By: Relevance
“…On the other hand, a very low isolation rate (2.3%) was observed in a study conducted in Kuwait by Mokaddas et al (6,20,21).…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, a very low isolation rate (2.3%) was observed in a study conducted in Kuwait by Mokaddas et al (6,20,21).…”
Section: Discussionmentioning
confidence: 85%
“…2,3,19,23,28,63,65 The spectrum of bacteria causing neonatal sepsis and postinfectious hydrocephalus also differs between developing and developed countries. 32,36 In developed countries, Group B Streptococcus, Escherichia coli, and Listeria monocytogenes most commonly cause neonatal sepsis. In the developing world, gram-negative organisms, but rarely Group B Streptococcus, predominate.…”
Section: Hydrocephalus Etiologymentioning
confidence: 99%
“…In the developing world, gram-negative organisms, but rarely Group B Streptococcus, predominate. 32,36 Furthermore, differences in bacterial speciation may depend on the season: cases of postinfectious hydrocephalus had a greater prevalence of Acinetobacter species in the ventricular CSF of Ugandan infants during the rainy season. 36 Another study in Uganda found that the peak incidence of postinfectious hydrocephalus was related to climate, with infection-onset peaks in the intermediate period between rainy and dry seasons.…”
Section: Hydrocephalus Etiologymentioning
confidence: 99%
“…Higher birth rates and limited perinatal care contribute to a greater burden of care for hydrocephalus in LMICs 57 (for example, there are 100,000-250,000 new infant cases of hydrocephalus annually in sub-Saharan Africa alone 41 ). In addition to the expected burden of congenital hydrocephalus in LMICs, climate-driven neonatal ventriculitis of unknown pathogenesis has recently been identified as one of the chief causes of infant hydrocephalus (60% of cases in Uganda) [58][59][60][61] . In sub-Saharan Africa, rates of neonatal sepsis are estimated to be 170 per 1,000 births, with a corresponding mortality of 10 deaths per 1,000 births 62 .…”
Section: Treating Hydrocephalus In Lmicsmentioning
confidence: 99%